Konsep Integrasi Ilmu (Non Dikotomi Pengetahuan) Dalam Pandangan Islam - Ummu Khairin Nisa; , Hasan Hasan; Zulkarnaen (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Integration of science is the process of harmonizing science with religion. However, it is still found in society that people are more concerned with general science than religious science, and vice versa. So this research is intended to describe the purpose of science integration, and the relationship between science and Islam, problems and solutions to the integration of Islam and science, and the importance of integration. The method in this research is library research method. The results show that the integration of science is a complementary construction process, where science serves to complement theological knowledge (faith), and vice versa. The relationship between Islam and science is that science provides tools and accelerates progress, while Islam determines the purpose and direction of human efforts. The importance of integration is due to the fact that Muslims need a system of science that can fulfill their material and spiritual needs, where the current scientific method is not able to meet these needs. Meanwhile, the problems of integration in the community are the lack of facilities and infrastructure, the educational background of teachers, etc. The solution to overcome these problems is to improve the quality of teachers, integrate science with religious disciplines, make God's creation as a learning infrastructure, provide Islamic religious education laboratories, and others.